Role of gender sensitisation training in combating gender-based bullying, inequality, and violence - Ashwani Kumar Upadhyay; Komal Khandelwal; Jayanthi Iyengar; Geetanjali Panda (Cogent Business & Management, 2023)
This study investigates the vital role of gender sensitisation training in resolving gender-based bullying, inequality, and violence in Indian organisations. The research examines the multifaceted forms of gender-related issues using the theoretical frameworks of the Social Dominance Theory, Gender Role Socialisation Theory, and Social Identity Theory. The qualitative study uses an exploratory approach to examine gender-based bullying, inequality, and violence in Indian academic and professional settings. Furthermore, the research examines whether gender sensitisation training is only a compliance measure or an effective strategy for promoting gender equality. According to preliminary studies, while gender sensitisation training implementation in India has been delayed, its primary focus has been statutory responsibilities. Despite global and local attempts to achieve gender equality, significant efforts are still required to improve the efficacy of gender sensitisation training measures. Although some organisations have used technology for training online, considerable improvements are needed. Finally, this study emphasises the importance of gender sensitisation training as a transforming instrument rather than a symbolic gesture, emphasising the need for comprehensive and long-term methods to achieve gender equality in Indian organisations. Summary: The authors of this study represent a diverse group of academics and researchers. The interaction of technology, people, and strategy inspires the group. Dr Jayanthi's research focuses on gender violence in the publicly accessible digital sphere. The entire research group is interested in learning about the role of gender sensitisation training in addressing violence, inequality, and bullying motivated by gender. Ms Geetanjali is eager to learn and comment on the subtleties of gender-based bullying. The team is trained in using various tools and strategies to do qualitative and quantitative research.
Keywords: 650; gender inequality; gender sensitisation; gender-based bullying; gender-based violence; training